Correlation between Estrogen ReceptorÎ² (ERÎ²), Neurofilament Protein (NF), and Protein Gene Product 9.5 (PGP9.5) Expressions as a Marker of Pain on Adenomyosis Etiopathogenesis (Majalah Kedokteran Bandung, 2021)
Adenomyosis is a pathological condition characterized by the presence of endometrial glands and stroma within the myometrium. Endometrial like cells development was influenced by local inflammatory reactions, increases local estradiol due to asynchromatized estrogen synthesis (ERÎ²) and then stimulated to proliferation and fibrosis, are also irritation on small nerve fibers in women with painful characterized symptoms on adenomyosis. There are expressions of neurofilament protein (NF) and protein gene product 9.5 (PGP 9.5) is a highly specific pan-neuronal marker for microfilament nerve fibers and is related to presenting pain with adenomyosis symptoms. A retrospective immunohistochemical study of thirty samples histopathological of adenomyosis as study groups and 30 with control groups between 25–49 ages which were established at Dr. Hasan Sadikin General Hospital and the satellites in April 2014–May 2015. This case-control analyzed ERÎ², NF, and PGP 9.5 expressions compared and correlation between study groups and controls. The results showed there were significant differences in expression of ERÎ², NF, and PGP 9.5 on adenomyosis higher than the control study (p3 (sensitivity 93%; specificity 46%), PGP 9.5>4 (sensitivity 90%; specificity 67%). Odds Ratio (CI 95%) ERÎ²>6= 4.67; NF >3=12.25; PGP 9.5 >4=24.75 (p
Keywords: Adenomyosis; estrogen receptors Î²(ERÎ²); protein neurofilament (NF); protein gene product 9.5(PGP9.5)